Caracterização de águas produzidas provenientes de campos petrolíferos onshore do Estado de Sergipe - Ribeiro, Vaniele Souza (2013)
In this work, five water produced samples from oil fields onshore (land) of the Sergipe State were characterized. The physico-chemical parameters such as pH, conductivity, turbidity, suspended solids, biochemical oxygen demand (BOD) and content of oil and grease (TOG) were determined. The concentrations of anions (Br-, Cl-, F-, NO3- and SO42-) and cations (Ca2 +, K +, Mg2+, Na +, and NH4+) were determined by ion chromatography (IC). The total arsenic was determined by hydride generation atomic fluorescence spectrometry (HG AFS). For trace metals determination (Ba, Cd, Cr, Cu, Fe, Li, Mn, Ni, Pb, V and Zn) was used inductively coupled plasma mass spectrometry (ICP-MS). The limit of quantification (LOQ) ranged between 0.07 ìg L-1 (Cd e V) and 22 ìg L-1 (Fe). The precision was expressed as relative standard deviation (RSD) ranged between 0.03% (Na+) and 7.39% (F-). The values of recoveries obtained were between 85 ± 3% (Zn) and 112 ± 1% (Li). The results were compared to the values established by Resolution 430/2011 of the National Council for the Environment (CONAMA). To evaluate the data, the principal component analysis (PCA) and hierarchical cluster analysis (HCA) were used. The concentrations of BOD, TOG, Ba, Mn and Fe were higher than those allowed by law, for some samples. The pH and concentration of As, Pb, Cr, Cu and Ni, for all samples, were consistent with established values. The conductivity, turbidity, suspended solids, concentration of anions, cations, Li and V are not required by law. The concentrations of Cd and Zn were below the LOQ of the method. In general, all the samples have very similar profiles with relatively close found values for all parameters. It was found that the samples have characteristics and inorganic constituents, which may cause damage to environment or generate drawbacks when used for reinjection. Therefore, the monitoring and characterization the produced water from onshore oil fields are very important for proper treatment of this effluent.